Pengenalan BISMETIK++ Bagi Keluarga Petani Nelayan di Gampong Langung Kabupaten Aceh Barat - Farah Diana; Afrizal Hendri; Sufal Diansyah (Universitas Teuku Umar, 2017)
FGD results with some fishermen/farmers obtained several problems including the fish seed price is quite expensive in Aceh Barat regency, the price of feed (pellets) quite expensive fish, the fish often escape from confinement containers because the tide or rip nets, the process of cultivation is done traditionally, fish consumption rates did not increase when compared to the price of feed has continued to increase as well as the management of the business which has not been neat. As for the purpose of this activity, namely the partners get IPTEKS about cultivation of fish (the production of fish feed is independent, the enlargement with the application bioflok in bismetik container, organic vegetable production from aquaculture wastes, processing crops for mother-housewife fishermen). The approach that was used against the subject's partner is a method of lecture and lab course. While the way or stages for the success of the programs include problem identification, needs analysis, preparation of programs, program implementation, monitoring and evaluation based on the indicators of success of the program, the workshop results by presenting program stakeholders and reporting. As for the activities that have been carried out, namely the enlargement the enlargement of this fish where fish is one of the many business segments performed the fish farmers. Next up is the making of fish feed activities, activities that have been undertaken, namely booking engine feed feed creation and outreach to the community of the village directly, and so on aquaponik activities, namely activities manage wastes the rest of metabolism the fish with the utilization of plants in outdoor aquaponik.